Inflammation, Senescence and MicroRNAs in Chronic Kidney Disease - Carmona, Andres; Guerrero, Fatima; Jimenez, Maria Jose; Ariza, Francisco; Agüera, Marisa L.; Obrero, Teresa; Noci, Victoria; Muñoz-Castañeda, Juan Rafael; Rodríguez, Mariano; Soriano, Sagrario; Moreno, Juan Antonio; Martin-Malo, Alejandro; et al. (Frontiers in Cell and Developmental Biology, 2020)
ABSTRACT Background: Patients with chronic kidney disease (CKD) show a chronic microinflammatory state that promotes premature aging of the vascular system. Currently, there is a growth interest in the search of novel biomarkers related to vascular aging to identify CKD patients at risk to develop cardiovascular complications. Methods: Forty-five CKD patients were divided into three groups according to CKD-stages (predialysis (CKD4-5), hemodialysis (HD) and kidney transplantation (KT)). In all these patients, we evaluated the quantitative changes in miRNAs, CD14+C16++ monocytes number, and microvesicles (MV) concentration (both total MV, and monocytes derived MV (CD14+Annexin V+CD16+)). To understand the molecular mechanism involved in senescence and osteogenic transdifferentation of vascular smooth muscle cells (VSMC), these cells were stimulated with MV isolated from THP-1 monocytes treated with uremic toxins (txMV). Results: A miRNA array was used to investigate serum miRNA profiles in CKD patients. Reduced expression levels of miRNAs-126-3p, -191-5p and -223-3p were observed in CKD4-5 and HD patients as compared to KT. This down-regulation disappeared after KT, even when lower glomerular filtration rates (eGFR) persisted. Moreover, HD patients had higher percentage of proinflammatory monocytes (CD14+CD16++) and MV derived of proinflammatory monocytes (CD14+Annexin V+CD16+) than the other groups. In vitro studies showed increased expression of osteogenic markers (BMP2 and miRNA-223-3p), expression of cyclin D1, β-galactosidase activity and VSMC size in those cells treated with txMV. Conclusion: CKD patients present a specific circulating miRNAs expression profile associated with the microinflammatory state. Furthermore, microvesicles generated by monocytes treated with uremic toxins induce early senescence and osteogenic markers (BMP2 and miRNA-223-3p) in VSMC.